2015
DOI: 10.3892/mmr.2015.4230
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic immunotherapeutic effects of Lycium barbarum polysaccharide and interferon-α2b on the murine Renca renal cell carcinoma cell line in vitro and in vivo

Abstract: Novel therapeutic strategies to improve clinical efficacy in patients with renal cell carcinoma (RCC) are required. The possibility of combination therapy with Lycium barbarum polysaccharides (LBP) and recombinant interferon (IFN)-α2b remains to be elucidated in RCC. The present study investigated the putative synergistic immunotherapeutic roles of LBP and IFN-α2b against RCC in vitro and in vivo. The mouse RCC cell line, Renca, was used for in vitro experiments. Treatment of the cells with a combination of LB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“… 21 Previous studies had shown that LBP by itself could inhibit tumor growth in mice. 22 - 24 Our previous study demonstrated that LBP3 is the major component of LBP in inhibiting H22 tumor growth. Thus, we supposed LBP3 might enhance the antitumor activity of Dox in H22 tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 98%
“… 21 Previous studies had shown that LBP by itself could inhibit tumor growth in mice. 22 - 24 Our previous study demonstrated that LBP3 is the major component of LBP in inhibiting H22 tumor growth. Thus, we supposed LBP3 might enhance the antitumor activity of Dox in H22 tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 98%
“…As one of important bioactive components, Lycium barbarum polysaccharide (LBPS) prevents 6-OHDA-caused PC12 cell apoptosis partially via reactive oxygen species- (ROS-) nitric oxide (NO) pathway [ 14 ]. In both in vitro and in vivo experiments, LBPS shows synergistic immunotherapeutic effects with interferon- α 2b on renal cell carcinoma [ 15 ]. In high-fat diet-induced insulin resistance animal models, LBPS is confirmed to be an antioxidant against insulin resistance via activating phosphatidyl inositol 3-kinase (PI3K)/AKT/nuclear factor erythroid 2 p45 related factor 2 (Nrf2) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and development of human cutaneous squamous cell carcinoma is an extremely complex process, which is controlled by a variety of genes and various factors and is associated with abnormal proliferation, differentiation, and apoptosis of tumor cells. Previous studies have shown that LBP, the main effective component of Lycium barbarum, has shown in antitumor studies some efficacy that it can inhibit the growth of a variety of tumor cells and has the advantages of low toxicity, fewer side effects, and availability [6][7][8][9][10]. In recent years, autophagy is emerging as a new strategy for cancer prevention and treatment and has been proven to be closely related to tumor cell growth and proliferation, as well as malignant metastasis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Lycium barbarum polysaccharides (LBP), the main bioactive ingredient of Chinese herbal medicines and food supplements, have antioxidation, antiaging, and neuroprotective effects [6]. It is also worth noting that LBP has been shown to exhibit significant biological activity in inhibiting tumor growth both in vitro and in vivo, including bladder, cervical, colon, liver, and kidney cancers [6][7][8][9][10]. Autophagy is an evolutionarily conserved catabolic process that recycles proteins and damaged organelles and plays an important regulatory role in the balance of cell survival and death.…”
Section: Introductionmentioning
confidence: 99%